Natural resource rents, economic dynamics and structural change: a capital theoretic approach - Faber, Malte; Proops, John L. R. (Ecological economics, 1993)
This paper concerns the effects of natural resource rents on the dynamics and structural change of an economy which is accumulating capital. The concept of rent is developed and the determinants of natural resource rents in the real world are discussed. To examine the long-run effects of rents on the price system and economic structural change, a neo-Austrian capital theoretic model is developed. This is presented in input-output form, and the corresponding prices for the model are derived so that a consistent set of national accounts for the model can be found. Natural resource use is introduced into the model with natural resource rents forming a further element of value-added. The model is then further generalised with the dynamics of capital accumulation being determined through a savings function which itself varies with the rate of return on capital. This model is used to simulate the effect on economic dynamics and structural change of two natural resource rent profiles, both of which follow the Hotelling rule. The effects of these two cases on the model are examined through the corresponding sets of national accounts.